[Over rough seas ; Flower country [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Probe takes a look at the plight of Filipino fishermen recruited by Eastern Houzon Maritime Sciences, Inc. to work in Taiwan; and Holland famous for its flower industry.
Over rough seas (20 min.) -- Flower country (10 min.)
VHS.
Keywords: Filipinos -- Employment. -- Taiwan; Holland -- Description and travel